Intellectual property rights management in developing countries - Nyatlo, Sheila Mavis; Caballero, Catherina; Fernando, M. A. M. (Daya Pub. House, 2012)
Papers presented at the International Advanced Training Course on Intellectual Property Rights (IPR) for NAM and Other Developing Countries, held at New Delhi and Manesar during, 12-17 July 2010.